Football cannot restart soon during the COVID-19 emergency! A critical perspective from the Italian experience and a call for action - Corsini, A.; Bisciotti, G. N.; Eirale, C.; Volpi, P. (British Journal of Sports Medicine, 2020)
The aim of this letter is a call for action for all the football medicine community to recommend to the football governance the maximal caution on the decision when to restart sport activity. Moreover, a specific protocol to check cardiological, pulmonary and, in general, systemic sequelae of COVID-19 before resuming sporting activities should be considered.